Do protoperithecia smell perithecia? - R. L. Metzenberg (Fungal Genetics Reports, 1993)
Long ago, Howe and Prakash (1969, Can. J. Genet. Cytol. 11:689-705) reported a surprising finding. Working with Neurospora tetrasperma, they initiated crosses by plating conidia onto part of a lawn of protoperithecia of the opposite mating type.